Modal Logic question about provability/ countermodels.


This statement is provable. You can turn it into an equivalent implication: ¬□(□A → B) → □(□B → A)

Then make the hypothesis that the first term is true and show that the second follows.

The first term is equivalent to

◇¬(□A → B)

◇(□A ∧ ¬B)

From which follows that

□A ∧ ◇¬B


Then in any possible world, we have


From which we can trivially show that in this possible world,

□B → A

This is true in any possible world, so we've shown that the second term of the implication follows from the first.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.